Pengaruh Risiko Pembiayaan Musyrakah dan Risiko Pembiayaan Murabahah terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia - Cut Afrianandra; Evi Mutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2014)
The purpose of this study is to examine and analyze the effect of Musharaka financing risk and the risk of murabaha financing to profitability in Indonesian Islamic banks. The target population of this research is Islamic Banks in Indonesia that registered for three consecutive years. Based entire population, there are 11 Islamic bank for 3 years with 33 observation data. The multiple regression analysis model in used to test the hypothesis. The results of this study indicate that the risk of Musharaka financing and murabahah risks simultaneously affect on profitability. In partial Musharaka financing risk and the risk of murabaha financing have positive influances on profitability.